2007
DOI: 10.1159/000111144
|View full text |Cite
|
Sign up to set email alerts
|

Desipramine Induces Apoptotic Cell Death through Nonmitochondrial and Mitochondrial Pathways in Different Types of Human Colon Carcinoma Cells

Abstract: Cytotoxic effects of desipramine on human colon carcinoma HT29 and HCT116 cells were examined. Desipramine reduced the viability of HT29 cells in a concentration-dependent manner, but failed to cause any significant change in the viability of HCT116 cells by the concentration up to 50 µmol/l, at which an approximately 60% reduction of the viability of HT29 cells was observed. Despite their different sensitivities, desipramine caused the nonoxidative apoptotic damage to both of them. In contrast to HT29 cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
28
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 76 publications
4
28
0
Order By: Relevance
“…These findings are in agreement with previous studies which found that DMI inhibited cell proliferation and induced apoptosis in osteosarcoma cells, prostate cancer, colon cancer, renal tubular and glioma cells (14,15,(26)(27)(28)(29) and caused cell cycle arrest in colon cancer cells (13). In this study, we found a decrease in mRNA expression of Bcl-2 and survivin.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These findings are in agreement with previous studies which found that DMI inhibited cell proliferation and induced apoptosis in osteosarcoma cells, prostate cancer, colon cancer, renal tubular and glioma cells (14,15,(26)(27)(28)(29) and caused cell cycle arrest in colon cancer cells (13). In this study, we found a decrease in mRNA expression of Bcl-2 and survivin.…”
Section: Discussionsupporting
confidence: 94%
“…It is conceivable that DMI induces apoptosis via the mitochondrial pathway, which causes release of cytochrome c from the mitochondria to the cytoplasm which subsequently activates caspases to induce DNA fragmentation. A previous study found that DMI may cause non-oxidative apoptotic damage to different types of carcinoma cells through either a non-mitochondrial or a mitochondrial pathway, which may be related to different sensitivities of these cancer cells to this drug (13,28). Moreover, DMI caused arrest of cell cycle progression in either the G0/G1 or G2/M phase, which might be dependent upon the concentration of DMI.…”
Section: Discussionmentioning
confidence: 99%
“…7). Interestingly, p53 levels in the presence of desipramine alone were very low—in agreement with the observation that although desipramine induces apoptosis in a mitochondrial-dependent manner, HCT116 cells are not especially sensitive to this agent [26]. All three platinum drugs induced measureable levels of p53, with oxaliplatin having the most overt effect under these conditions.…”
Section: Resultssupporting
confidence: 82%
“…(27) In lung cancer, TCAs induce cell death via histamine and adrenergic receptors by blocking Gα s and PKA, CREB and ATF1 signaling. (13) Additional studies have confirmed the induction of cell death by TCAs(10,28) while others found associations with reduced incidence of certain cancers. (29) Also, previous work on models of glioma showed a potential synergistic effect between chlorimipramine (a TCA) and dexamethasone,(11,30) while use of the TCA imipramine in combination with citalopram, an SSRI, induced apoptosis of acute myeloid leukemia cells.…”
Section: Discussionmentioning
confidence: 94%